1991
DOI: 10.1126/science.253.5026.1394
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origin of Io's Fast Sodium

Abstract: Neutral sodium emissions encircling Jupiter exhibit an intricate and variable structure that is well matched by a simple loss process from Io's atmosphere. These observations imply that fast neutral sodium is created locally in the Io plasma torus, both near Io and as much as 8 hours downstream. Sodium-bearing molecules may be present in Io's upper atmosphere, where they are ionized by the plasma torus and swept downstream. The molecular ions dissociate and dissociatively recombine on a short time scale, relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 19 publications
2
31
0
1
Order By: Relevance
“…The observed morphology and inferred velocity distribution of the "stream" feature observed by Schneider et al (1991b) are consistent with fresh molecular ions NaX + (where X is any atom or molecular fragment) being the originator of the fast Na (Schneider et al 1991b, Wilson andSchneider 1994). In this process, NaX + ions are presumably created near Io either from charge-exchange reactions of torus ions with neutral NaX molecules in Io's exosphere or from reactions of other molecular ions (e.g., SO + , SO + 2 , S + 2 ) with atomic Na in Io's exosphere (Johnson 1994).…”
Section: High-speed Sodium: Molecular-ion-produced "Stream"mentioning
confidence: 77%
See 1 more Smart Citation
“…The observed morphology and inferred velocity distribution of the "stream" feature observed by Schneider et al (1991b) are consistent with fresh molecular ions NaX + (where X is any atom or molecular fragment) being the originator of the fast Na (Schneider et al 1991b, Wilson andSchneider 1994). In this process, NaX + ions are presumably created near Io either from charge-exchange reactions of torus ions with neutral NaX molecules in Io's exosphere or from reactions of other molecular ions (e.g., SO + , SO + 2 , S + 2 ) with atomic Na in Io's exosphere (Johnson 1994).…”
Section: High-speed Sodium: Molecular-ion-produced "Stream"mentioning
confidence: 77%
“…Spencer and Schneider (1996) categorize the high-velocity features into (1) a downstream "spray" of fast sodium atoms produced when Na + ions in the torus undergo resonant charge exchange with neutral Na in the Io atmosphere, (2) a "sheet" or "stream" of fast sodium atoms ejected tangentially from the direction of motion of fresh pickup ions; this feature may be produced from dissociation or dissociative recombination of molecular ions that were recently ejected from Io (Schneider et al 1991b, Wilson and Schneider 1994, Johnson 1994, and (3) "directional features" or "jets" produced by prompt neutralization of torus pickup ions very near Io (e.g., Spencer and Schneider 1996), by neutralization of atmospheric sodium ions that were driven radially outward from Io by Pedersen currents in Io's ionosphere (e.g., Wilson and Schneider 1999), or by atmospheric Na atoms ejected by single elastic collisions with corotating torus ions (e.g., Pilcher et al 1984, Sieveka andJohnson 1984). These features are often as bright as the B cloud, and all three might contribute to an extended disk of sodium atoms seen more than 400 jovian radii from the Jupiter system (e.g., Mendillo et al 1990).…”
Section: Implications For Io's Neutral Sodium Cloudsmentioning
confidence: 99%
“…This is because molecular sodium is efficiently destroyed by photodissociation and gas-phase chemistry, which further produce atomic sodium. The fast sodium atoms observed in the form of a narrow jet leading Io in its orbit about Jupiter are thought to be produced by dissociation of NaX + in Io's plasma torus (Schneider et al 1991b). Wilson and Schneider (1994) suggested that these molecular ions are formed near Io's exobase and are picked up by the corotating field.…”
Section: Discussionmentioning
confidence: 98%
“…and potassium clouds (Brown 1973, Trafton 1975 around Surface and subsurface frost temperature measurements Io require the existence of a source for these compounds. were recently obtained from the position of several weak Regarding sodium, Schneider et al (1991) and Wilson and bands (in the 2-Ȑm range) due to SO 2 frost, which are Schneider (1994) have shown that the fast Na atoms, which temperature dependent and probe different depths within constitute one of the main components of the sodium the ice layer (Schmitt et al 1994). A surface frost tempera-cloud, are produced from the dissociation of sodium-bearture of 100 Ϯ 20 K was inferred, with, interestingly, an ing molecular ions (NaX ϩ ).…”
Section: Surface Temperatures From Position Of 71 Photochemical Modmentioning
confidence: 97%